Coal Town : the life and times of Dawson, New Mexico - Smith, Toby (Ancient City Press Santa Fe, NM, 1994)
A history of how Dawson began, its people, its customs and how it came to an end. Dawson was abandoned about 1951 when the coal industry declined.
Preface : Acknowledgments : Beginning : Socializing : Growing : Mining : Dying : Learning : Competing : Fighting : ending : Bibliograpy : Author Interviews
Includes Biographies
66722
Keywords: History -- Dawson (N.M.); Coal mines and mining -- History -- Dawson, New Mexico; Ghost towns -- New Mexico; History